A large neighborhood search heuristic to establish an optimal ad-hoc hubbing strategy in the wake of a large-scale airport outage. (October 2017) - Suh, Daniel; Ryerson, Megan S.
Abstract: Abrupt airport outages can cause diversions and fuel-critical situations for flights, leading to costly passenger misconnections. We develop a large neighborhood search heuristic to optimize the rerouting of flights bound for a disrupted airport to a hub airport that is not disrupted, with the goal of accommodating passengers on existing flights departing the non-disrupted hub. The objective of the heuristic is to identify and reroute flights to the ad-hoc hub(s) – non-disrupted hub airport(s) – that minimize the sum of passenger travel time and wait time. We minimize the passenger cost as the sum of passenger travel time to the diversion airport and wait time for a connecting flight at the ad-hoc hub airport, subject to on-board fuel and diversion airport capacity constraints. We use the heuristic to determine how a coordinated traffic management strategy could have diverted flights immediately following a real-world airport outage. Highlights: A heuristic that identifies an ad-hoc hubbing strategy in case of abrupt airport outages is proposed. The heuristic minimizes total passenger wait and travel time with constraints on onboard fuel and diversion airport capacity. Publicly available real-world aviation data are used. The results of this study indicate the value of collaboration in extreme events that impact the aviation system.